English Student Teachers’ Reflections on E-Portfolio Assessment - Sarlita D. Matra (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Assessment in teacher education has the primary goal of developing English student teachers as self-monitoring and self-assessing professionals who are able to learn reflectively from their experiences and practices. We need an assessment tool that enhances the capacity of English student teachers for self-assessment and reflection on their levels of developing knowledge and practice. E-portfolios engage students in authentic assessment that allows them to see how and what they are learning, and how they are progressing over time. E-portfolios acknowledge the value in diverse approaches to learning and students have the opportunity to use multiple strategies for demonstrating their knowledge. In this study, the E-portfolio offers a rare opportunity to conduct an in-depth exploration of, and reflection on learning. It allowed students to practice, self-evaluate, and make adjustments or corrections before completing their final work. Several English student teachers noted that the technology gave them the opportunity to be reflective in ways they could not, prior to employing the E-portfolio.